Gingival Crevicular blood an alternative site for assessment of blood glucose levels - Tharakeswari, R. (International Journal of Pharmaceutical & Biological Archive, 2017)
Aim: Diabetes mellitus is a common chronic disease associated with increased morbidity and mortality. Periodontitis has been considered as the sixth complication of diabetes mellitus. Most of the diabetic patients present with this problem which goes undiagnosed. Patients with periodontitis will have bleeding in the gingival crevicular area which itself can be used to assess the glycemic status. Even in those who don’t have bleeding minimal probing in the gingival crevicular area will give us the required sample. Study design: To evaluate and assess the reliability of the gingival crevicular blood glucose as a diagnostic tool to assess blood glucose level. Two groups of 25 each as group A (Diabetics) and group B (Nondiabetics) accounting to a sample size of 50 were taken for the study. Results: Gingival crevicular blood glucose values were compared with capillary finger blood glucose and conventional venous blood glucose. The values in the group were statistically analyzed using Pearson’s rank correlation. The paired samples revealed an intra class statistically significant correlation (p < 0.001). Conclusion: Considering the correlation between the gingival crevicular blood glucose and the other two standard methods, assessment of crevicular blood glucose can be used as a routine in small clinics, PHC’S, dental OPD’s. The technique is safe, easy to perform and is also cost effective. Hence gingival crevicular blood glucose estimation can be used as a tool to assess the blood glucose level with accuracy.